The importance of historical poems in the teaching of language and literature (based on the historical poem «Kabanbai batyr») - Тлеубердина, Гульден; Батыр, Мөлдір (Pedagogy and Psychology, 2022)
In the article, the author analyses the research and genre descriptions of historical poems, focusing on the literary features of the historical song "Kabanbay". Author do the analysis with the help of expressions to show that the historical songs can be the composition which tell the story of different events that took place in each period of time. The importance of historical poetry as a folklore heritage in social life was shown by analysing the opinions of literary critics.